Development and validation of a Women’s Empowerment in Migration Index (WEMI): A Pilot Application with Women Migrants in Bangladesh - Alvi, Muzna; Ratna, Muzna; Sufian, Farha; Khan, Mohidul Hoque; Ringler, Claudia (Centre of Excellence for Development Impact and Learning, 2023)
There is ample data and literature that shows how women’s experiences in low-paid, short-term migration vary from those of men, and that experiences are linked to women’s empowerment – captured by the interrelated dimensions of resources, agency, and achievements. While considerable attention is paid to understanding the generalized notion of women’s empowerment, it is also key to distinguish empowerment in specific realms, including economic empowerment, agriculture, health and nutrition, and migration. To better understand the agency of female migrants, a Women’s Empowerment in Migration Index (WEMI) was developed. This brief discusses work to assess this index with data from women migrants in the Bangladesh to West Asia migration corridor.